2017
DOI: 10.1002/14651858.cd011645.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for acute hepatitis B infection

Abstract: Low or very low quality evidence suggests that progression to chronic HBV infection was higher in people receiving lamivudine compared with placebo, no intervention, or entecavir. Low quality evidence suggests that interferon may increase the adverse events after treatment for acute HBV infection. Based on a very low quality evidence, there is currently no evidence of benefit of any intervention in acute HBV infection. There is significant uncertainty in the results and further RCTs are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 78 publications
0
21
2
4
Order By: Relevance
“…In previous research, these markers at first HBsAg‐positive serology were associated with reduced risk of delayed HBsAg seroclearance and developing chronic infection . Second, anti‐HBV containing ART was infrequently given to HBV‐infected individuals during the study period and the treatments provided (mostly lamivudine) were unlikely to provide a major prophylactic effect on either HBV acquisition or HBsAg seroclearance during the acute phase . As such, we were unable to provide any assessment on the role of anti‐HBV‐containing ART in our study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In previous research, these markers at first HBsAg‐positive serology were associated with reduced risk of delayed HBsAg seroclearance and developing chronic infection . Second, anti‐HBV containing ART was infrequently given to HBV‐infected individuals during the study period and the treatments provided (mostly lamivudine) were unlikely to provide a major prophylactic effect on either HBV acquisition or HBsAg seroclearance during the acute phase . As such, we were unable to provide any assessment on the role of anti‐HBV‐containing ART in our study.…”
Section: Discussionmentioning
confidence: 77%
“…5,10 Second, anti-HBV containing ART was infrequently given to HBV-infected individuals during the study period and the treatments provided (mostly lamivudine) were unlikely to provide a major prophylactic effect on either HBV acquisition 17 or HBsAg seroclearance during the acute phase. 23 As such, we were unable to provide any assessment on the role of anti-HBV-containing ART in our study. Third, individuals with established chronic infection had a shorter follow-up than those with standard HBsAg Finally, we had a small sample size which did not allow us to study determinants of delayed HBsAg seroclearance in multivariable analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Most commonly, biomarkers of liver damage with a PT(INR) !1.6, bilirubin !170 lM (10 mg/dL) or clinical signs of impaired liver function, such as ascites or encephalopathy are used. A meta-analysis from Cochrane 2017, found that studies of treatment of acute hepatitis B are of low quality and that evidence to recommend such treatment is lacking [43]. However, with regards to the potentially serious consequences and the lack of severe side-effects, it is reasonable to recommend treatment as described below in cases where a severe disease progression is suspected, as outlined in the recently published guideline from the British Transplantation Society [44].…”
Section: Treatment Of Hepatitis B Virus Infectionmentioning
confidence: 99%
“…Pored napora, pokušaj pronalaska optimalne terapije analizom nekoliko različitih studija ostaje kontroverzan. U jednoj takvoj studiji, objavljenoj 2017. godine, autori nisu mogli da utvrde relevantne razlike između ishoda simptomatske i antivirusne terapije, ali ni sa sigurnošću da tvrde da one ne postoje, usled pristrasnih i podataka slabijeg kvaliteta u studijama koje su analizirali (16).…”
Section: Diskusijaunclassified